Cytisus multiflorus: source of antioxidant polyphenols - Pereira, Olívia R. (2013)
The present study investigates the phenolic composition and the antioxidant capacity of an ethanolic extract from flowers of C. multiflorus. As determined by HPLC-DAD, ESI-MSn and NMR combined analysis, this extract was mainly composed of chrysin-7-O-β-D-glycopyranoside, and also contained considerable amounts of rutin, a dihydroxyflavone isomer of chrysin and glycosidic derivatives of luteolin and apigenin. The C. multiflorus ethanolic extract exhibited high DPPH scavenging activity and reducing power with EC50 of 13.4 ± 0.6 and 95.7 ± 4.6 µg/mL, respectively. The exposure of human hepatoblastoma HepG2 cells to the non-toxic concentrations of the extract (50 or 200 µg/mL) resulted in a decreased rate of ROS production in a concentration dependent manner. Moreover, the mixture of standards that simulated the phenolic composition of the plant afforded a protection of about 50% in intracellular ROS production. Hence, the gathered results suggest that C. multiflorus polyphenols are closely associated to its antioxidant properties.